Outcomes for recurrent oral cavity squamous cell carcinoma. (November 2022) - Contrera, Kevin J.; Zafereo, Mark E.; Yaniv, Dan; Roberts, Diane B.; Gillenwater, Ann M.; Hanna, Ehab Y.; Weber, Randal S.; Myers, Jeffrey N.; Chang, Edward I.; Garvey, Patrick B.; Hanasono, Matthew M.; Yu, Peirong; et al.
Highlights: 5-year overall survival after salvage oral cavity surgery was 44% Recurrent stage, disease-free interval, and previous radiation influenced survival. Median hospital and professional charges were approximately 130, 000. 80% of patients had intelligible speech, oral intake, and no tracheostomy. Abstract: Objectives: We sought to determine overall survival (OS), prognostic factors, cost, and functional outcomes after surgery for locally recurrent oral cavity squamous cell carcinoma (OCSCC). Materials and Methods: We retrospectively reviewed 399 cases of locally recurrent OCSCC from 1997 to 2011, of which 259 patients were treated with salvage surgery. Survival and prognostic factors were evaluated using univariable and multivariable Cox regression, the Kaplan-Meier method, and the log-rank test. Results: The 5-year OS for patients undergoing surgical salvage, nonsurgical therapy, or supportive care was 44.2%, 1.5%, and 0%, respectively. For patients who underwent surgical salvage, 133 (51%) patients experienced a second recurrence at a median of 17 months. Factors associated with OS included disease-free interval ≤ 6 months ( P =. 0001), recurrent stage III-IV disease ( P <. 0001), and prior radiation ( P =. 0001). Patients with both advanced stage and prior radiation had a 23% 5-year OS, compared with 70% for those with neither risk ( P <.001). Functionally, 85% of patients had > 80% speech intelligibility and 81% were able to eat by mouth following salvage surgery. Of the patients who required tracheostomy, 78% were decannulated. The adjusted median hospital and professional charges for patients were 129, 696 (range 9, 238-956, 818). Conclusions: Patients with recurrent OCSCC who underwent salvage surgery have favorable functional outcomes with half of alive at 5 years but poorer OS for advanced disease, disease-free interval ≤ 6 months, and prior radiation. Additionally, treatment is associated with high cost, and about half of patients ultimately develop another recurrence.